Multifunctional conductive hydrogel and preparation method thereof
By adopting a three-dimensional network structure and specific raw material combination in multifunctional conductive hydrogels, the water loss and adhesion of conductive hydrogels in biological applications and wearable devices is solved, and high-performance and low-cost multi-functional water is achieved. Gel preparation, suitable for rehabilitation training monitoring and treatment equipment.
Patent Information
- Application Number
- CN202411250035.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The existing multifunctional conductive hydrogels have problems such as water loss and drying, difficulty in adhesion and peeling in biological applications and wearable devices, and high-end equipment and costly preparation methods limit their wide application.
Multifunctional conductive hydrogel using a three-dimensional network structure, through the interpenetration structure of PEDOT:PSS conductive polymer, acrylamide monomer and β-cyclodextrin copolymer gel network, gallic acid is added as a bond bridge, and glycerol is combined as Water retention agent forms a hydrogel with excellent mechanical properties and biocompatibility.
It achieves super tensile, antibacterial, anti-water loss, high swelling, peeling on demand, good UV and visible light transmission, biocompatibility and anti-oxidation properties within the strain range of 0-600%. , reduces the preparation cost and improves the customizable morphology of the material.
Smart Images

Figure CN119119367A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomaterials and flexible wearable health equipment, and in particular relates to a multifunctional conductive hydrogel and a preparation method thereof. Background Art
[0002] Multifunctional conductive hydrogels are a new type of hydrogel that organically combines a hydrophilic matrix with a conductive medium. They not only have the high water content, good biocompatibility and flexibility of traditional hydrogels, but also have excellent conductive properties by introducing conductive components (such as metal nanoparticles, carbon-based nanomaterials, etc.). This unique combination makes conductive hydrogels show great application potential in many fields. At present, flexible sensors with excellent electrical and mechanical properties for various purposes have been successfully prepared by combining conductive materials such as graphene oxide (reduced graphene oxide), silver nanowires (AgNWs), MXene nanosheets, PEDOT:PSS, and carbon nanotubes (CNTs) and conductive polymers with elastomeric composite substrates.
[0003] At present, a large number of methods for preparing hydrogels have been developed, but there are still various defects, such as easy dehydration and drying, and difficulty in peeling off wounds, which severely limit their functions and application fields, especially in biological applications and wearable devices. With the continuous development of materials science and biotechnology, the preparation technology of conductive hydrogels has developed rapidly, and its performance has also been significantly improved. For example, conductive hydrogels with complex shapes and structures can be prepared by 3D printing technology, which provides more possibilities for its application in the fields of bioelectronic interfaces and tissue engineering. Among them, the recently reported N,N,N-trimethylethaneamine chloride-based hydrogel was obtained by using attapulgite rigid particles and polyvinyl alcohol (PVA) semi-crystalline double networks. It has good conductivity and is used for flexible electronic devices and electrochemical energy storage. However, 3D printing technology is only suitable for complex structures based on fiber structures, and the mechanical properties are relatively poor. Moreover, the preparation methods of hydrogels with these complex structures are inseparable from high-end equipment, high costs and harsh conditions. Therefore, it is urgent to develop a low-cost, customizable morphology, multifunctional and excellent hydrogel preparation scheme. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a multifunctional conductive hydrogel and a preparation method thereof, wherein the hydrogel has the characteristics of super stretchability within a large strain range of 0-600%, antibacterial property, anti-water loss, high swelling property, on-demand peeling, good UV protection and visible light transmittance, good biocompatibility and excellent antioxidant properties, and can be used for rehabilitation training monitoring and treatment equipment under conditions of large joint deformation.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A multifunctional conductive hydrogel has a three-dimensional network structure, wherein the three-dimensional network structure is formed by introducing gallic acid into an interpenetrating network, wherein the interpenetrating network is formed by introducing PEDOT:PSS conductive polymer into a copolymer gel network, wherein the copolymer gel network is formed by grafting acrylamide monomers onto a β-cyclodextrin skeleton, and the gallic acid serves as a bond bridge between the hydrogel networks.
[0007] PEDOT:PSS is a conductive polymer network that interpenetrates with the copolymer gel network to form a hydrogel network;
[0008] Such an interpenetrating network gives the hydrogel a more stable and strong structure, and the three-dimensional network structure has uniform pores with an average pore size of 20 to 30 μm.
[0009] The raw materials for preparing the conductive hydrogel include PEDOT:PSS (based on poly(3,4-ethyldioxythiophenyl) polystyrene sulfonate), acrylamide monomer, ammonium persulfate, N,N-methylenebisacrylamide, β-cyclodextrin, and gallic acid; all of which have excellent biocompatibility. The above raw materials are added to the solution after proportioning, and the solution contains glycerol and water. The mass ratios of the solvent are 1:2 to 1:4 for glycerol and water, 2:3 to 2:3.5 for glycerol and acrylamide, 200:1 to 200:2 for glycerol and ammonium persulfate: 80:1 to 40:1, 5:1 to 5:2 for glycerol and PEDOT:PSS, and 40:1 to 20:1 for glycerol and β-cyclodextrin and gallic acid.
[0010] The acrylamide monomer is grafted onto the β-cyclodextrin skeleton. At high temperature, ammonium persulfate generates free radical reaction sites on the β-cyclodextrin main chain. The generated free radicals attack the double bonds in the monomer to generate a copolymer gel network. The PEDOT:PSS conductive polymer is introduced into the above copolymer gel network to form an interpenetrating network. Gallic acid containing three phenolic hydroxyl groups is introduced into the above interpenetrating network. The addition of gallic acid introduces abundant hydrogen bonds, which constitute bond bridges connecting the hydrogel networks. The abundant hydrogen bonds contribute to the formation of the hydrogel and enhance the mechanical properties of the hydrogel. Glycerol is used to replace part of the water in the solvent to reduce the formation of ice crystals and reduce the evaporation of water in the open air environment.
[0011] The multifunctional hydrogel is a three-dimensional network porous structure with uniform pores, good conductivity, stretchability, water retention, frost resistance, high swelling, adhesion, on-demand peeling, good UV protection and visible light transmittance, good biocompatibility and excellent antioxidant properties, as well as excellent antibacterial properties.
[0012] The thickness of the multifunctional hydrogel can be arbitrarily adjusted within a range greater than 20 μm;
[0013] The hydrogel is divided into a thin hydrogel and a thick hydrogel, the thin hydrogel has a thickness of 20 μm < ≤ 100 μm, and adopts a frameless hydrophilic mold;
[0014] Thick hydrogels with thickness >100 μm were prepared using either hydrophilic or hydrophobic molds.
[0015] The corresponding mold is selected according to the thickness requirements of the prepared hydrogel. The hydrogel morphology can be customized during the preparation process. The required mold is customized to the corresponding size and pattern using a laser cutting machine, so that hydrogels of different shapes and thicknesses can be customized according to different application scenarios.
[0016] Due to the addition of PEDOT:PSS, the multifunctional hydrogel has excellent conductivity (conductivity>0.025S / m), the addition of gallic acid brings abundant hydrogen bonds to the hydrogel network, enhances the cohesion of the hydrogel network, and provides the hydrogel with excellent stretchability (0-600% wide range elastic deformation), and glycerol as a water retaining agent brings good water retention (water retention rate>65% after 30 days at room temperature) and antifreeze (still has good stretchability after 15 days of storage at-40°C), and the hydrogel has a certain swelling property (>324%), and gallic acid also brings good adhesion to the hydrogel (strong adhesion on various substrates such as glass, plastic, skin, metal, etc.), due to the cold, the hydrogen bonds of the hydrogel network are re-entangled to achieve on-demand peeling, in addition, due to the porous structure of the hydrogel, its air permeability (>3000g / m 3 / 12h), and the hydrogel has good light transmittance (>100%), UV protection (200nm-400nm UV transmittance is reduced), good biocompatibility (cell survival rate>95%), and the polyphenol structure also brings the hydrogel good antioxidant properties (DPPH free radical scavenging rate is as high as 86.3%) and antibacterial properties (Staphylococcus aureus inhibition rate>82%, Escherichia coli inhibition rate>90%).
[0017] A method for preparing a multifunctional conductive hydrogel comprises the following steps:
[0018] Step 1: Mix acrylamide, N,N-methylenebisacrylamide, PEDOT:PSS, β-cyclodextrin and gallic acid;
[0019] Step 2: After mixing, place the mixture into a mixed solution of glycerol and deionized water, and stir evenly at room temperature to obtain a conductive hydrogel precursor solution;
[0020] Step 3: Add ammonium persulfate to the hydrogel precursor solution and mix well, put the above precursor solution into a mold, and obtain a conductive hydrogel under heating conditions.
[0021] In the step 1, the mass fraction of acrylamide is 40-60%, the mass fraction of N,N-methylenebisacrylamide is 0.1%-0.2%; the mass fraction of PEDOT:PSS is 5%-10%; the mass fractions of β-cyclodextrin and gallic acid are both 1%-5%, the mass fraction of ammonium persulfate is 0.5%-0.1%, and the rest are water and glycerol; the above ingredients are added to glycerol and water.
[0022] The mass ratios are as follows: the ratio of glycerol to water is 1:2 to 1:4, the ratio of glycerol to acrylamide is 2:3 to 2:3.5, the ratio of glycerol to N,N-methylenebisacrylamide is 200:1 to 200:2, the ratio of glycerol to ammonium persulfate is 80:1 to 80:2, the ratio of glycerol to PEDOT:PSS is 5:1 to 5:2, and the ratio of glycerol to β-cyclodextrin and gallic acid is 40:1 to 20:1.
[0023] In step 2, magnetic stirring is adopted, the speed of magnetic stirring is 500r / min to 800r / min, and the time of magnetic stirring is 10min to 15min.
[0024] The heating condition in step 3 is to carry out the polymerization reaction in a vacuum drying oven at 50° C.-80° C. for 1 to 4 hours.
[0025] The multifunctional conductive hydrogel is used in electronic skin, intelligent prostheses and robot surface skins, flexible biosensors and other intelligent wearable devices and health monitoring fields.
[0026] Beneficial effects of the present invention:
[0027] In the present invention, acrylamide monomer is grafted onto a β-cyclodextrin skeleton, and at high temperature, ammonium persulfate generates free radical reaction sites on the β-cyclodextrin main chain, and the generated free radicals attack the double bonds in the monomer to generate a copolymer gel network, and a PEDOT:PSS conductive polymer is introduced into the copolymer gel network to form an interpenetrating network, and gallic acid containing three phenolic hydroxyl groups is introduced into the interpenetrating network. The addition of gallic acid introduces abundant hydrogen bonds, and these hydrogen bonds constitute bond bridges connecting the hydrogel networks, wherein the abundant hydrogen bonds contribute to the formation of the hydrogel and enhance the mechanical properties of the hydrogel, wherein glycerol is used to replace part of the water in the solvent to reduce the formation of ice crystals and reduce the evaporation of water in an open air environment;
[0028] The hydrogel has the characteristics of super stretchability within a large strain range of 0-600%, antibacterial property, water loss prevention, high swelling, on-demand peeling, good UV protection and visible light transmittance, good biocompatibility and excellent antioxidant properties.
[0029] The multifunctional conductive hydrogel prepared by the present invention uses polyacrylamide, beta-cyclodextrin and gallic acid as raw materials, all of which are substances with excellent biocompatibility. The preparation process is simple, green and environmentally friendly.
[0030] The multifunctional conductive hydrogel prepared by the present invention has good deformation ability and good skin adhesion, high water retention, high swelling capacity, good antioxidant ability, excellent UV protection ability and high visualization. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a picture of the PEDOT:PSS / polyacrylamide-β-CD hydrogel of the present invention.
[0032] Figure 2 Water loss rate of the multifunctional conductive hydrogel at 25°C.
[0033] Figure 3 It is the light transmittance of the multifunctional conductive hydrogel in the range of 200-900nm.
[0034] Figure 4 This is the swelling performance diagram of the multifunctional conductive hydrogel.
[0035] Figure 5 This is the air permeability diagram of the multifunctional conductive hydrogel.
[0036] Figure 6 Stretchability and recoverability of multifunctional conductive hydrogels.
[0037] Figure 7 The strong adhesion of multifunctional conductive hydrogels on different substrates.
[0038] Figure 8 Conductivity of multifunctional conductive hydrogels.
[0039] Fig. 9 Antioxidant capacity of multifunctional conductive hydrogels.
[0040] Fig.10 Antibacterial ability of multifunctional conductive hydrogels.
[0041] Fig.11 Biocompatibility of multifunctional conductive hydrogels.
[0042] Fig.12 Schematic diagram summarizing the properties of multifunctional conductive hydrogels.
[0043] Fig.13 SEM image of the cross section of the multifunctional conductive hydrogel. DETAILED DESCRIPTION
[0044] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0045] Example 1
[0046] like Figure 1 The following is a direct picture of the conductive hydrogel.
[0047] The preparation of a multifunctional conductive hydrogel is completed by the following specific steps:
[0048] 0.8g PEDOT:PSS was dissolved in a mixed solvent of 4g glycerol and 8g water and mixed at 500r / min on a magnetic stirrer, and then 6g acrylamide monomer, 0.02g N,N-methylenebisacrylamide, 0.1g β-cyclodextrin, and 0.1g gallic acid were added to the mixed light blue liquid in sequence until the liquid became clear and transparent to obtain a hydrogel precursor solution. The hydrogel precursor solution was added to the mold and placed in a vacuum drying oven at 60°C for 4h to obtain a multifunctional conductive hydrogel.
[0049] In this example, Figure 2 As shown in Figure 2, the water loss rate of the hydrogel within 30 days was 32%, which showed good water retention performance. Figure 3 The hydrogel has an extraordinary visible light transmittance and good ultraviolet light absorption properties in the ultraviolet region. Figure 4 As shown, the hydrogel swells by 323% within 24 hours, which is a low swelling hydrogel, thus better ensuring the adhesion stability of the interface. Figure 5 The water vapor permeability of the hydrogel within 12 hours reached 3300 g / m 2 , Figure 6 , 7 , 8 respectively show that the hydrogel has good mechanical properties, excellent interfacial adhesion and good electrical conductivity. Fig. 9 , 10 The hydrogels have antioxidant and antibacterial properties. Fig.11 The hydrogel has good biocompatibility. Fig.12 The excellent properties of the hydrogel are summarized, providing a wider range of application scenarios for the hydrogel, such as wound treatment and monitoring.
[0050] Fig.13 This is a scanning electron microscope image of the cross section of the hydrogel. It can be seen that the hydrogel has a three-dimensional network structure with a pore size of approximately 20 μm. The three-dimensional network structure makes the hydrogel more stable and durable.
[0051] Example 2
[0052] The preparation of a multifunctional conductive hydrogel is completed by the following specific steps:
[0053] 0.9g PEDOT:PSS was dissolved in a mixed solvent of 4g glycerol and 8g water and mixed at 500r / min on a magnetic stirrer, and then 7g acrylamide monomer, 0.04g N,N-methylenebisacrylamide, 0.15g β-cyclodextrin, and 0.15g gallic acid were added to the mixed light blue liquid in sequence until the liquid became clear and transparent to obtain a hydrogel precursor solution. The hydrogel precursor solution was added to the mold and placed in a vacuum drying oven at 60°C for 4h to obtain a multifunctional conductive hydrogel.
[0054] The functional properties were also evaluated, and it was found through comparison that the hydrogel prepared in Example 1 had more excellent performance.
[0055] Example 3
[0056] The preparation of a multifunctional conductive hydrogel is completed by the following specific steps:
[0057] 0.95g PEDOT:PSS was dissolved in a mixed solvent of 4g glycerol and 8g water and mixed at 500r / min on a magnetic stirrer, and then 8g acrylamide monomer, 0.03g N,N-methylenebisacrylamide, 0.15g β-cyclodextrin, and 0.1g gallic acid were added to the mixed light blue liquid in sequence until the liquid became clear and transparent to obtain a hydrogel precursor solution. The hydrogel precursor solution was added to the mold and placed in a vacuum drying oven at 60°C for 4h to obtain a multifunctional conductive hydrogel.
[0058] The functional properties were also evaluated, and it was found through comparison that the hydrogel prepared in Example 1 had more excellent performance.
[0059] The invention has the characteristics of super-strong stretchability within a large strain range of 0-600%, antibacterial property, water loss prevention, high swelling property, on-demand peeling, good UV protection and visible light transmittance, good biocompatibility and excellent anti-oxidation.
[0060] Finally, the method of the present application is only a preferred implementation scheme and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the protection and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A multifunctional conductive hydrogel, characterized in that: The three-dimensional network structure is formed by introducing gallic acid into an interpenetrating network, the interpenetrating network is formed by introducing PEDOT:PSS conductive polymer into a copolymer gel network, the copolymer gel network is formed by grafting acrylamide monomers onto a β-cyclodextrin skeleton, and the gallic acid serves as a bond bridge between hydrogel networks.
2. A multifunctional conductive hydrogel according to claim 1, characterized in that: PEDOT:PSS is a conductive polymer network that interpenetrates with the copolymer gel network to form a hydrogel network; The three-dimensional network structure has uniform pores with an average pore size of 20 to 30 μm.
3. The multifunctional conductive hydrogel according to claim 1, characterized in that: The raw materials for preparing the conductive hydrogel include PEDOT:PSS, acrylamide monomer, ammonium persulfate, N,N-methylenebisacrylamide, β-cyclodextrin, and gallic acid; The above raw materials are added to the solution after proportioning. The solution contains glycerol and water in the following mass ratios: 1:2 to 1:4, 2:3 to 2:3.5, 200:1 to 200:2, 80:1 to 80:2, 5:1 to 5:2, and 40:1 to 20:1 for glycerol and β-cyclodextrin and gallic acid, respectively.
4. The multifunctional conductive hydrogel according to claim 1, characterized in that: The thickness of the multifunctional hydrogel can be arbitrarily adjusted within a range greater than 20 μm; The hydrogel is divided into a thin hydrogel and a thick hydrogel, the thin hydrogel has a thickness of 20 μm < ≤ 100 μm, and adopts a frameless hydrophilic mold; Thick hydrogels with thickness >100 μm were prepared using either hydrophilic or hydrophobic molds.
5. A method for preparing a multifunctional conductive hydrogel according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Mix acrylamide, N,N-methylenebisacrylamide, PEDOT:PSS, β-cyclodextrin and gallic acid; Step 2: After mixing, place the mixture into a mixed solution of glycerol and deionized water, and stir evenly at room temperature to obtain a conductive hydrogel precursor solution; Step 3: Add ammonium persulfate to the hydrogel precursor solution and mix well, put the above precursor solution into a mold, and obtain a conductive hydrogel under heating conditions.
6. The method for preparing a multifunctional conductive hydrogel according to claim 5, characterized in that: In the step 1, the mass fraction of acrylamide is 40-60%, the mass fraction of N,N-methylenebisacrylamide is 0.1%-0.2%; the mass fraction of PEDOT:PSS is 5%-10%; the mass fractions of β-cyclodextrin and gallic acid are both 1%-5%, the mass fraction of ammonium persulfate is 0.5%-0.1%, and the rest are water and glycerol; the above ingredients are added to glycerol and water.
7. The method for preparing a multifunctional conductive hydrogel according to claim 6, characterized in that: The mass ratios are as follows: the ratio of glycerol to water is 1:2 to 1:4, the ratio of glycerol to acrylamide monomer is 2:3 to 2:3.5, the ratio of glycerol to N,N-methylenebisacrylamide is 200:1 to 200:2, the ratio of glycerol to ammonium persulfate is 80:1 to 80:2, the ratio of glycerol to PEDOT:PSS is 5:1 to 5:2, and the ratio of glycerol to β-cyclodextrin and gallic acid is 40:1 to 20:
1.
8. The method for preparing a multifunctional conductive hydrogel according to claim 5, characterized in that: In step 2, magnetic stirring is adopted, the speed of magnetic stirring is 500r / min to 800r / min, and the time of magnetic stirring is 10min to 15min.
9. The method for preparing a multifunctional conductive hydrogel according to claim 5, characterized in that: The heating condition in step 3 is to carry out the polymerization reaction in a vacuum drying oven at 50° C.-80° C. for 1 to 4 hours.
10. The multifunctional conductive hydrogel according to any one of claims 1 to 9, characterized in that: The multifunctional conductive hydrogel is used in the fields of electronic skin, intelligent prostheses and robot surface skins, intelligent wearable devices of flexible biosensors, and health monitoring.
Citation Information
Patent Citations
Stretchable transparent conductive hydrogel and preparation method thereof
CN110256694A
Transparent stretchable high-ionic-conductivity hydrogel and preparation and application thereof
CN111072998A
Preparation method and application of conductive hydrogel based on MAA / PEDOT:PSS
CN111675797A
Preparation of double-network conductive hydrogel and application of double-network conductive hydrogel in strain sensor
CN111763334A
Water-based conductive adhesive and preparation method thereof
CN111961421A
